2015
DOI: 10.1108/lr-10-2014-0105
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing strategies on traditional vegetables for supporting food security in Kilosa District, Tanzania

Abstract: Purpose – The purpose of this paper is to examine knowledge sharing on traditional vegetables for supporting food security among farmers and other communities in Kilosa district, Tanzania. Design/methodology/approach – A case study design was employed. Semi-structured questionnaires with both open- and closed-ended questions were used to collect quantitative data in three wards of Kilosa District in Tanzania. Interviews were used to coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…More farmers are venturing in the production of amaranth because it needs less inputs, has short growth period, is fairly resistant to drought, and is attacked by fewer pests, and the market demand is rising. This shows an improving trend from earlier reports which indicated that the vegetables are semicultivated and are mostly collected from the wild [ 26 , 27 ]. In all the discussions in both Kenya and Tanzania, it was reported that at least 30% of community members grow amaranth for either sale, home consumption, or both.…”
Section: Resultssupporting
confidence: 60%
“…More farmers are venturing in the production of amaranth because it needs less inputs, has short growth period, is fairly resistant to drought, and is attacked by fewer pests, and the market demand is rising. This shows an improving trend from earlier reports which indicated that the vegetables are semicultivated and are mostly collected from the wild [ 26 , 27 ]. In all the discussions in both Kenya and Tanzania, it was reported that at least 30% of community members grow amaranth for either sale, home consumption, or both.…”
Section: Resultssupporting
confidence: 60%
“…Tabak, Khoong [7], developed a framework (model) that is used by a variety of stakeholders, including funders, practitioners, and researchers, to help them better understand the needs of all stakeholders and systems, the model can also be used to help improve efforts to get research findings out to practitioners and policymakers, as well, in particular, models from non-health fields may have been overlooked or under-represented. [16] provides agricultural development planners with a framework for integrating indigenous knowledge about traditional vegetables with scientific knowledge in local communities, with the goal of enhancing food security in Tanzania, the study recommends that there is a need to increase awareness and knowledge about the importance of traditional vegetables, particularly their nutritional value, among youth because they are unfa-miliar with the production, consumption, and processing of traditional vegetables. [17] developed a theoretical framework for examining knowledge sharing behavior, which is critical for organizational change and national reforms, as well as for surviving in a world of intense competition.…”
Section: Framework For Research Knowledge Disseminationmentioning
confidence: 99%
“…Stimulation to meaningful policies, institutional networks and qualification initiatives in several levels in order to overcome the restrictions and effectively incorporate the ICTs into the agricultural development process [7][8][9].…”
Section: Potential Impacts Of Knowledge Management For Agricultural D...mentioning
confidence: 99%
“…The result is that knowledge managementobtain, systematize and share human capital -became the most important task in the countries [6]. In the delimitation of the nations' agricultural sector, the development of human capital is considered as a fundamental aspect of the intelligence agenda established in the national strategies of agricultural development [7], for its management may maximize the mechanisms for the sustainable development, and favor the economic, social and environmental development nation-wise [8]. These arguments reinforce the premise that knowledge is a production factor that has become more and more meaningful in modern agriculture [9].…”
Section: Introductionmentioning
confidence: 99%